Structural adjustment programmes adversely affect vulnerable populations: a systematic-narrative review of their effect on child and maternal health - Michael Thomson; Alexander Kentikelenis; Thomas Stubbs (Frontiers Media S.A., 2017)
Abstract Structural adjustment programmes of international financial institutions have typically set the fiscal parameters within which health policies operate in developing countries. Yet, we currently lack a systematic understanding of the ways in which these programmes impact upon child and maternal health. The present article systematically reviews observational and quasi-experimental articles published from 2000 onward in electronic databases (PubMed/Medline, Web of Science, Cochrane Library and Google Scholar) and grey literature from websites of key organisations (IMF, World Bank and African Development Bank). Studies were considered eligible if they empirically assessed the aggregate effect of structural adjustment programmes on child or maternal health in developing countries. Of 1961 items yielded through database searches, reference lists and organisations' websites, 13 met the inclusion criteria. Our review finds that structural adjustment programmes have a detrimental impact on child and maternal health. In particular, these programmes undermine access to quality and affordable healthcare and adversely impact upon social determinants of health, such as income and food availability. The evidence suggests that a fundamental rethinking is required by international financial institutions if developing countries are to achieve the Sustainable Development Goals on child and maternal health.